FRI0534 Incidence and type of malignancies in patients with juvenile idiopathic arthritis: a retrospective single-center cohort study. (23rd January 2014) - Bisdorff, B.; Radon, K.; Hartmann, B.; Molz, J.; Hager, L.; Michels, H.; Haas, J. P.
Abstract : Background: The risk of malignancies in patients with Juvenile idiopathic arthritis (JIA) irrespective of their treatment is currently being under discussion. (1 -5 ) Objectives: The aim of this study was to determine whether patients with JIA have an elevated cancer risk and if so, which cancer types are increased. Methods: Standardized incidence ratios (SIRs) were calculated for overall cancer, lymphoma, leukaemia and skin cancer for 4080 JIA patients, that took part in the study, and that had been admitted to the German Centre for Rheumatology in Children and Young People, Garmisch-Partenkirchen, between 1952 and 2010. Data had been obtained via a postal questionnaire survey and compared to the German cancer registry. Results: A response of 65% was obtained, participant's age ranging between 2 and 74 years. SIR for all cancers was 0.49 (95% confidence interval 0.38-0.62) with an elevated overall cancer risk for the younger age groups (0-19 yrs. 3.21; 1.04-3.67, 20-29 yrs. 2.31;1.29-3.81; 30-39 yrs. 1.71; 1.14-2-47). In contrast, cancer risk for the older age groups were statistically significantly reduced (40-49 yrs. 0.34; 0.19-0.56; 50-74 yrs. 0.10; 0.04-0.2). For lymphoma the combined SIR for all age groups was 0.60 (0.16-1.54), for leukaemia 1.51(0.49-3.53) and skin cancer 2.28 (1.43-3.46) with again increased risk in the younger age groups. Conclusions: This study suggests that the risk of cancer might be increased in younger JIA patients (< 40 years), especially with regards to skin cancer and lymphoma. A second part of the study will determine whether incidence was influenced by medication or environmental factors. References: Bernatsky S, Rosenberg AM, Oen KG, Duffy CM, Ramsey-Goldman R, Labrecque J, et al. Malignancies in juvenile idiopathic arthritis: a preliminary report. The Journal of rheumatology. 2011;38(4):760-3. Epub 2011/01/18. Beukelman T, Haynes K, Curtis JR, Xie F, Chen L, Bemrich-Stolz CJ, et al. Rates of malignancy associated with juvenile idiopathic arthritis and its treatment. Arthritis and rheumatism. 2012;64(4):1263-71. Epub 2012/02/14. Nordstrom BL, Mines D, Gu Y, Mercaldi C, Aquino P, Harrison MJ. Risk of malignancy in children with juvenile idiopathic arthritis not treated with biologics. Arthritis care & research. 2012. Epub 2012/04/19 Simard JF, Neovius M, Hagelberg S, Askling J. Juvenile idiopathic arthritis and risk of cancer: a nationwide cohort study. Arthritis and rheumatism. 2010;62(12):3776-82. Epub 2010/09/10. Thomas E, Brewster DH, Black RJ, Macfarlane GJ. Risk of malignancy among patients with rheumatic conditions. International journal of cancer Journal international du cancer. 2000;88(3):497-502. Epub 2000/10/31 Acknowledgements: The authors would like to thank the "Förderverein für das Rheumakranke Kind e.v." for financial support. Disclosure of Interest: None Declared